Microstructure, Phase Evolution, and Chemical Behavior of CrCuFeNiTiAlx High Entropy Alloys Processed by Mechanical Alloying - Anay del Ángel-González; Greysi D. Tapía-Higuera; Ibeth Rivera-Ortiz; José A. Castillo-Robles; José A. Rodríguez-García; Carlos A. Calles-Arriaga; José G. Miranda-Hernández; Enrique Rocha-Rangel (Entropy, 2023)
High entropy alloys (HEAs) of the type CrCuFeNiTi-Alx were processed through mechanical alloying. The aluminum concentration was varied in the alloy, to determine its effect on the HEAs’ microstructure, phase formation, and chemical behavior. X-ray diffraction studies performed on the pressureless sintered samples revealed the presence of structures composed of face centered cubic (FCC) and body centered cubic (BCC) solid-solution phases. Since the valences of the elements that form the alloy are different, a nearly stoichiometric compound was obtained, increasing the final entropy of the alloy. The aluminum was partly responsible for this situation, which also favored transforming part of the FCC phase into BCC phase on the sintered bodies. X-ray diffraction also indicated the formation of different compounds with the alloy’s metals. Bulk samples exhibited microstructures with different phases. The presence of these phases and the results of the chemical analyses revealed the formation of alloying elements that, in turn, formed a solid solution and, consequently, had a high entropy. From the corrosion tests, it could be concluded that the samples with a lower aluminum content were the most resistant to corrosion.